THE EFFECTIVENESS OF SCIENTIFIC APPROACH TO EARLY CHILDHOOD INTEREST IN LEARNING THE HOLY QUR’AN - Eva Eriani; Tiara Tiara; Indra Bangsawan; Tria Marini; Nova Adi Kurniawan (-, 2023)
Al-Quran is the holy book of Muslims that must be introduced from an early age. Introducing the holy Qur’an in the Early Childhood institution is over reciting, writing, and memorizing versicle. The approaches used by teachers however do not convenient to students’ characteristics. In addition, the teachers rarely integrate the themes of material to the verses of the holy Qur’an, such as: the environment, the universe, natural phenomena, water, air, and fire. The learning process will be better if the students understand the meaning in it. This can be completed by a scientific approach for their thinking skill. This study aims to identify the effectiveness of the scientific approach to interest of children aged 5-6 years in learning the Qur’an. This research is quantitative research with one group pretest-posttest design. The data were gained through observation, and were analyzed by using the T-test, namely paired sample test. The results proved that t count 5,436 ≥ t table 1,76 with significance value of 0,00 ≤ 0,05.  It thus believes that Ha is accepted and Ho is rejected, which means the scientific approach is effective to students’ interest in learning the Qur'an.